The Earth Formation Process Analysis According to Science and Quran - Sri Amanda Rizky; Winarti (Proceeding International Conference on Religion, Science and Education, 2023)
The process of the formation of the earth has been explained in the Qur'an which has been interpreted by many scholars. Theories of the formation of the earth have also been expressed by previous scientists such as the big bang theory, nebula theory, planetesimal theory, tidal theory, and dust cloud theory. The formation of the earth can be observed not only based on science. But the process of the formation of the earth has been written in the Qur'an long before the creation of the earth and its contents. This paper aims to find out the process of creating the earth based on the Qur'an and science. The writings were arranged using library Research Method. With data collection techniques, namely reviewing scientific articles, books, or other sources of information in print or electronic form that are in accordance with the topic discussed in this paper. The data is then reviewed and analyzed so that conclusions are obtained. Allah wrote the process of creating the earth in the Koran, which was then explained by the big bang theory. In the big bang theory, the beginning of the creation of the earth stems from a big explosion whose effects are felt to this day. It is hoped that this article can add insight and faith to readers.